1990
DOI: 10.1111/j.1600-9657.1990.tb00389.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo fractures of endodontically treated posterior teeth restored with amalgam

Abstract: The cumulative survival rate (retention of both cusps) and the fracture pattern of 1639 endodontically treated posterior teeth were assessed in a retrospective study. All teeth had an MO/DO or an MOD cavity restored with amalgam without cuspal overlays. The 20-year survival rate of teeth with an MO/DO cavity was markedly higher than that of teeth with an MOD cavity. The lowest survival rate was found for the upper premolars with an MOD cavity: 28% of these teeth fractured within 3 years after endodontic therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0
14

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 15 publications
2
89
0
14
Order By: Relevance
“…4,11,14 Full amalgam coverage of sufficient strength is capable of restoring form and function and providing adequate fracture resistance in restored teeth. 10,13,26 Clinical observations have indicated high survival rates (from four to 15 years) of amalgam restorations with cusp coverage.…”
Section: Secondary Caries Alpha (α)mentioning
confidence: 99%
See 3 more Smart Citations
“…4,11,14 Full amalgam coverage of sufficient strength is capable of restoring form and function and providing adequate fracture resistance in restored teeth. 10,13,26 Clinical observations have indicated high survival rates (from four to 15 years) of amalgam restorations with cusp coverage.…”
Section: Secondary Caries Alpha (α)mentioning
confidence: 99%
“…ness of the cusp, leading to cusp elongation, can result in deflection of the cusp and increased susceptibility of endodontically-treated maxillary premolars to fracture. 4,11 Full cuspal coverage is advised to protect the remaining cusps from splitting.…”
Section: Secondary Caries Alpha (α)mentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Numerous studies have reported a high incidence of fracture in endodontically treated maxillary premolars. 2,5,6 Susceptibility to fracture is the result of the loss of marginal ridges and the pulp chamber roof during access preparation 2,7,8 and is a concern, particularly in maxillary premolars, because their anatomy facilitates separation of the cusps during mastication. 9 Fractures in the unsupported tooth structure can lead to restorative difficulties and even extraction if the tooth is unrestorable.…”
Section: Introductionmentioning
confidence: 99%